MONETARY EXPECTATIONS OF THE ROMANIAN EXECUTIVES REGARDING THE ADHERATION - Ramona DUMITRIU; Răzvan ŞTEFĂNESCU (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2006)
This paper explores the monetary expectations induced to the managers of Romanian firms by adheration. It is based on an investigation among twenty Romanian executives regarding the impact on adheration over monetary aspects: inflation, exchange rates and adoption of euro. We conclude that the results of the monetary policy in the last years made the executives confident that the Romanian authorities could maintain the monetary stability after theadheration.